2017
DOI: 10.1002/jee.20178
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Robotics Teams’ Collaboration Quality on Team Performance in a Robotics Tournament

Abstract: Background Working effectively in teams is an important 21st century skill as well as a fundamental component of the ABET professional competencies. However, successful teamwork is challenging, and empirical studies with adolescents concerning how the collaboration quality of team members is related to team performance are limited. Purpose/Hypothesis This study investigated the relationship between team collaboration quality and team performance in a robotics competition using multiple measures of team perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 63 publications
1
42
0
1
Order By: Relevance
“…Although the benefits of teamwork for engaging girls in engineering have been well documented (Busch-Vishniac & Jarosz, 2004;Cunningham & Lachapelle, 2014;Goodman et al, 2002;Menekse et al, 2017), research related to the impact of engineer role models and collaborative design goals on elementary students' engineering identities is more scarce. The present study builds on the existing literature by providing a detailed analysis of the experiences of 14 fifth-grade students, six girls and eight boys, as they moved through a 10-week, collaborative engineering design program run in partnership with engineering students from a nearby university, who served as near peer role models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the benefits of teamwork for engaging girls in engineering have been well documented (Busch-Vishniac & Jarosz, 2004;Cunningham & Lachapelle, 2014;Goodman et al, 2002;Menekse et al, 2017), research related to the impact of engineer role models and collaborative design goals on elementary students' engineering identities is more scarce. The present study builds on the existing literature by providing a detailed analysis of the experiences of 14 fifth-grade students, six girls and eight boys, as they moved through a 10-week, collaborative engineering design program run in partnership with engineering students from a nearby university, who served as near peer role models.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more collaborative approaches have been found to help retain girls in male-dominated subjects, such as computer science, engineering, and physics (Weisul, 2017). There exists a large body of research that shows collaboration can be used to engage a more diverse population in engineering and to help individuals construct engineering identities (Busch-Vishniac & Jarosz, 2004;Cunningham & Lachapelle, 2014;Goodman et al, 2002;Menekse et al, 2017;Pattison et al, 2018). Teamwork provides students with opportunities to contribute in a variety of ways, thereby placing value on diversity rather than creating hierarchies with competition.…”
Section: Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested that group learning offers a basis for social comparison and social learning (Solomon, Croft, & Lawson, 2010), and that teamwork quality and team diversity impact the effectiveness and quality of task completion (Curşeu, Schruijer, & Boroş, 2007;Menekse, Higashi, Schunn, & Baehr, 2017;Stevenson & Starkweather, 2010). For example, one study reported that students' approaches to understanding and solving a design task are influenced by their peers (Rivera-Reyes, Lawanto, & Pate, 2016).…”
Section: Project Management In Engineering Designmentioning
confidence: 99%
“…In contrast, characteristics of interactional styles within mixed gender groups strayed from social gender norms. (Schnittka & Schnittka, 2016, p. 1) The only research study exploring how students design that did not analyze verbal data was Menekse, Higashi, Schunn, and Baehr's (2017) study of "366 youths on 61 K-8 robotics teams that participated in a FIRST LEGO League Championship. Regression and mediation analyses were conducted to explore the relation between effective team collaboration and team performance" (p. 1).…”
Section: Research Question 3: Impact Of Engineering Design On Studentsmentioning
confidence: 99%